E-Learning Usability Evaluation Menggunakan Fuzzy Logic dan Usulan Alternatif Desain Interaktif Learning Management System (LMS) Chamilo - Arif Rinaldi Dikananda; Harry Budi Santoso; Raditya Danar Dana; Dadang Sudrajat (STMIK IKMI Cirebon, 2019)
E-Learning as well as learning media in general needs to be evaluated to find out and measure how much effectiveness, efficiency and user satisfaction is for the quality of the overall learning process. One effort that can be done to find out and evaluate the quality of learning is to use usability evaluation. Usability measurements require data derived from questionnaires presented using a Likert scale. The data illustrates the perceptions of users who have uncertainties because they are very subjective so they have the potential to cause misinterpretations. Fuzzy logic can be used to evaluate e-Learning reusability because fuzzy logic has the advantage of resolving a problem that contains uncertainty / ambiguity, which in this case is in accordance with the context of usability problems that are often presented in natural languages that have uncertainties, such as